2019
DOI: 10.1002/elan.201800705
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicinoids in Chili Habanero by Flow Injection with Coulometric Array Detection

Abstract: This study presents a sensitive electroanalytical method for the determination of capsaicinoids in chili extracts using flow injection with coulometric array detector. Flow injection method was developed based on the coulometric signal of capsaicinoids obtained by high performance liquid chromatography with coulometric detector (HPLC‐ECD). Capsaicinoids concentration in 18 chili samples from Yucatán México cultivated in different types of soils was quantified using UHPLC‐DAD and HPLC‐ECD and expressed in Scovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The work previously carried out by Morozova et al [44], showed that the type of soil had a significant effect on the content of capsaicinoids, reporting that habanero peppers grown in red soil had a higher concentration of capsaicinoids. This information and the results obtained in the present work demonstrate that the physicochemical composition of the soil affects the production of one type of metabolites over others.…”
Section: Discussionmentioning
confidence: 94%
“…The work previously carried out by Morozova et al [44], showed that the type of soil had a significant effect on the content of capsaicinoids, reporting that habanero peppers grown in red soil had a higher concentration of capsaicinoids. This information and the results obtained in the present work demonstrate that the physicochemical composition of the soil affects the production of one type of metabolites over others.…”
Section: Discussionmentioning
confidence: 94%
“…The calibration curve was prepared in the range of 0.005 to 0.08 mg mL −1 . The total capsaicinoids were reported as the sum of capsaicin and dihydrocapsaicin; Morozova et al described this method [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that the fruits have a high content of vitamin C and E and bioactive compounds such as polyphenols, carotenoids, and capsaicinoids. The fruits exhibit antioxidant, anticancer, and anti-inflammatory activities, mainly due to their capsaicin content [ 20 , 21 ]. However, there are few scientific studies on the nutritional and bioactive potential of its by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also focus on direct application of coulometric array detector for analysis of food antioxidants in flow injection mode. Specifically, it has been used for analysis of chlorpromazine [189], antioxidants in lettuce [190] and chili [191] extracts. Elimination of the separation step allows to identify the antioxidant capacity of large number sample in a single run within the shortest time possible.…”
Section: Coulometric Array Detectormentioning
confidence: 99%